A COGNITIVE-AFFECTIVE-BEHAVIORAL RESPONSES OF CUSTOMER EXPERIENCE (CAB-CE) MODEL FOR SERVICE DELIVERY IMPROVEMENT IN THE HEALTHCARE INDUSTRY - Wan Mustaffa, Wan Salmuni; Abdul Rahman, Rafiduraida; Ab Wahid, Hariyaty; Ahmad, Noor Lela; Ali@Hamid, Mass Hareeza; A Jalil, Emy Ezura (International Journal of Supply Chain Management, 2020)
The healthcare industry is shifting towards customer-focused similar to other service industries. The healthcare service providers and theorists have developed various measurement tools of customer experience (CE) to sustain the business. However, there are still unresolved issues related to CE measurement tools in the healthcare context need to be addressed. First, CE measurement tools still fail to capture the customers? journey towards healthcare service experiences truly. Second, the relevant variables representing each phase of CE, as well as their interrelationships, have rarely been explored and examined in the healthcare service industry. Thus, this research aims to develop and validate a CE measurement model by considering the relevant variables by representing three phases of customers? journey towards healthcare service delivery, namely cognitive, affective, and behaviour responses (CAB-CE). This research was conducted at Malaysian public hospitals. The customers who experienced service delivery at Malaysian public hospitals were selected as the respondents. The data were gathered via a questionnaire sent to the respondents using the convenience sampling technique. In total, 215 completed questionnaires were then proceeding to the data analysis stage. The structural equation modelling (SEM) using AMOS was performed to test the applicability of the model developed. SEM was also performed to simultaneously test the relationships among the variables of CE in a single model. The results revealed the validity and applicability of the CAB-CE model in measuring the CE in the healthcare service industry. Besides, the structural analysis has proven the relationships among the variables of customers? journey phases. Developing a CAB-CE model is hoped to contribute to the improvement of the existing CE measurement tools, both practically and theoretically, within the context of healthcare service.